The ANALISIS SISTEM SINKRONISASI DAN DISTRIBUSI DAYA GENSET PADA PROYEK DKUT PK-19 JIIPE GRESIK: Universitas Muhammadiyah Gresik - Mohammad Rizal Chasi Pratama; Ilham Arifin pahlawan (Universitas Muhammadiyah Gresik, 2025)
TThe DKUT PK-19 Infrastructure and Landscape Development Project at the JIIPE Gresik industrial area is a vital Bank Indonesia project requiring reliable and continuous power supply. To ensure energy availability, PT Jaya Teknik Indonesia (JTI) installed a backup power system consisting of two Mitsubishi generator units, MGS1500CL and MGS1300R L50. This study aims to analyze the synchronization and power distribution system between generators and their connection to the PLN grid. The research method includes field observation and operational parameter measurements, such as voltage, current, and frequency during testing, synchronization, and power distribution. Results indicate that synchronization between generators successfully maintains load balance with current differences below 5% across phases. The applied three-phase four-wire (3Φ-4W) distribution system effectively delivers power through the Main Distribution Panel (MDP) to subpanels throughout the project. The automatic synchronization system (auto-synchronizer) enhances fuel efficiency and voltage stability.